Vandetanib for the Treatment of Metastatic Medullary Thyroid Cancer - Degrauwe, Nils (Libertas Academica, 2012)
Medullary thyroid cancer (MTC) represents an aggressive form of thyroid malignancy. Some may occur spontaneously or can be associated with Multiple Endocrine Neoplasia syndromes, or Familial Medullary Thyroid Cancer syndrome. In these patients, the protooncogene RET (rearranged during transfection) is mutated. In patients who have unresectable or metastatic disease, the long term prognosis is poor. New treatments for this disease have focused on the use of targeted agents that inhibit the receptor tyrosine kinase of RET. One of these treatments, Vandetanib (Caprelsa, Astra Zeneca), recently has received approval from the Food and Drug Administration for the treatment of patients with progressive locally advanced and/or metastatic disease. This review highlights the studies that led to the drug’s approval, and discusses on the potential financial costs of treatment and side effects of this therapy. The main clinical studies evaluating Vandetanib for the treatment of other solid tumors will also be reviewed.